The Effect of Changes of Value and Behavior Model of Consuming in online social Network Using Integration of Buddhist Psychology for Thai Novices - Phoowachanathipong, Kamalas (Journal of International Buddhist Studies, 2017)
The purpose of this paper was to study the effect of changes of value and behavior model of consuming in online social network following integration of philosophy in Buddhist psychology of novices. The sample consisted of 78 grade 9 novices, participated the training program, of the General Education Section of PhraPariyattidhamma Schools in Nan Province. The random sampling were stratified random sampling based on the level of behavior of consuming in online social network and simple random. The samples were selected into three groups 1) the experimental group A consisting of 26 novices participated in the 3-day training and a 3-month project based learning 2) the experimental group B consisting of 26 novices participated in the 3-day training 3) the control group consisting of 26 novices who did not participate in any training and the research was designed Repeated Measure Design. The instruments used in this research were as follows: 1) Cognitive measurement of online social network consuming 2) Rationality of thinking measurement 3) Value of consuming in online social network measurement 4) Self-control measurement of online social network consuming 5) Online social network consuming behavior change measurement. The data were collected for 4 times: pre-test, post-test after training 1 , post-test after training 2 (3-month project based learning) and post-test after 1 month of Project based learning. The data were analyzed by Repeated measures ANOVA The results of this research were as follow: 1) The average score of value and behavior of consuming in online social network following integration of philosophy in Buddhist psychology both the experimental group A and B novices after the experiment were higher than before the experiment 2) No statistically significant interaction was found between training formats, number of measurements of cognitive and value of consuming in online social network measurement and Interaction between type of programs and times of measurement was found but found the interaction between the training formats, number of measurements of rationality of thinking , self-control measurement of online social network consuming and online social network consuming behavior at statistically significant .05 3) According to comparison of the average scores of each aspect with the training ,the most appropriate format of consuming in online social network behavior following integration of philosophy in Buddhist psychology of novices was Training 1 (experimental group A) which had higher mean score than Training 2 (experiment group B) and controlled group in 4 aspects: cognitive, self-control, value and behavior of consuming in online social network.